Career exploration and information literacy self-efficacy in social media usage among university students - Chia, Ching Yi (2024)
This research aimed to determine the relationship between career exploration, information literacy self-efficacy and social media usage among university students, and to determine whether information literacy self-efficacy and social media usage are able to predict career exploration. The research was designed as a quantitative cross-sectional correlational study. A purposive technique method was used, and 194 responses were collected throughout this research. The participants of this study were undergraduates, who were aged between 18 to 25, from different universities across Malaysia. The participants were approached by sending or showing the research survey physical face-to-face and also via social media platforms, such as Instagram, WhatsApp and “Little Red Book”. The questionnaire included informed consent, demographic information and three scales which were the Career Exploration Survey, Information Literacy Self-Efficacy Scale and Social Media Use Scale. The results of this research showed there are significant positive relationships between career exploration, information literacy self-efficacy and social media usage. It also showed that career exploration is significantly predicted by information literacy self-efficacy and social media usage. This research not only provided theoretical support for the Social Cognitive Career Theory’s Interest Model but also provided insights to the professionals in the Guidance and Counselling field, especially career counsellor, and undergraduate students on how career exploration affects information literacy self-efficacy and social media usage.